Keluar Dari Lingkaran Kemiskinan: Mobiliti Sosial di Kalangan Komuniti Pesisir Pantai, Kuala Terengganu - Nor Hayati, Sa'at (2010)
The issue of social change and transformation of coastal communities has been the subject of study in earlier landmark works, namely, by Firth (1940s), Ungku Aziz(1960s), and Ishak Shari (1980s). Today, it is found that coastal communities still consist mainly of fishermen who are often portrayed as marginalized, underdeveloped communities and left out of mainstream development. Members of the communities are often regarded as being "trapped within the circle of poverty and backwardness". However, processes of development and modernisation have directly or indirectly triggered changes among these communities while the latter too have undergone transformation. Based on this backdrop of backwardness and underdevelopment on the one hand, and transformation on the other, this study seeks to investigate the phenomenon of "getting out of the circle", vis., the phenomenon of social mobility among the coastal community by focusing on the coastal community in Kuala Terengganu. The theoretical position of the study is that there is no one single factor that can explain social mobility. On the contrary, the changes in the form of social mobility have to be seen within the analytical framework that emphasises multicausality or multi-factoral analysis. For upward social mobility, an individual requires the combination of a host of contributing factors such as education, economy, and socio-cultural, with the actor (human capital), family and community (social capital), as well as the state (structural factor) playing their roles simultaneously. A survey of 300 respondents has been administered, together with interviews and observations. The researcher also undertook a study of secondary materials and documents to analyse change and social mobility in the coastal community over time by using a historical perspective. In general, examined in the context of the history of the last sixty years or so within the coastal community, the fisherfolk is found to be on the decline as this occupation is becoming less and less popular. The study shows that a major transformation has taken place within the coastal community when four generations -- grandfather, father, respondent, and the respondent's son -- are compared. The role of the sea in providing the principal source of income or the principal occupation for members of the coastal community has become more heterogenous. This can be seen from the fact that the percentage of fishermen among the coastal community today only stands at 47 percent while other categories that make 53 percent, comprised of those doing administrative jobs (15 percent), business (22.7 percent) and labourers (15.3 percent). Based on the scale of mobility measurement constructed for the study, it is found that there are four patterns of mobility within the coastal community. Among individuals with better education and who have moved into commercial activities they are relatively more successful in 'getting out of the circle'. This study contributes towards the corpus of knowledge on sociology of development, particularly the study of change and social mobility of coastal communities. The outcome of this study strengthens the researcher's belief that only a proper understanding of the problems of coastal communities will assist the government and other stakeholders to formulate policy and plan programmes that can facilitate and manage change and development of marginalized communities so that they can be empowered.